Behavioral Economic Analysis of Brand Image, Service Quality, Social Media Quality, and Price Perception in Influencing Generation Z’s Purchase Intention for Cross-Border Personal Shopping Services: The Mediating Role of Trust - Yulfiswandi Yulfiswandi; Rosmawati Rosmawati (International Journal of Economics Development Research (IJEDR), 2025)
The jastip (personal shopper) business has become a popular trend in Indonesia in recent years. In the context of trade and consumption, jastip refers to a service where someone (jastip provider or personal shopper) offers to buy goods from a particular place or store at the request of another person (consumer). In return, the jastip provider will usually charge a service fee or commission on top of the price of the goods purchased. The research in this article aims to examine the factors that influence Purchase Intention on jastip, especially in generation Z, using the variables Brand Image, Service Quality, Social Media Quality, and Price Perception mediated by Trust. The study uses primary data that has been processed through the distribution of questionnaires in the form of Google Forms to the Batam City Community who have used jastip. A total of 311 respondent data that meet the criteria and are then processed using the SPSS program for respondent demographic data analysis and the SmartPLS program for hypothesis testing. The results of the study indicate that Brand Image, Service Quality, Social Media Quality, and Price Perception have a significant positive effect on Purchase Intention through Trust mediation. This study shows the importance of Trust as a mediator that connects all variables in influencing Purchase Intention towards Jastip among Generation Z in Batam City.